Narrative abilities and grammaticality of Russian heritage children: Evidence from Cyprus - Karpava, Sviatlana (Journal of Monolingual and Bilingual Speech, 2023)
Heritage language maintenance and development depend on the family language policy, language dominance, frequency of use, linguistic distance and similarities between the minority and the majority languages or (dia)lects of the society, as well as on the multi-directionality of cross-linguistic influence and accommodation. The present study investigates the narrative skills of Russian heritage children in Cyprus, with a focus on macro-structure (story structure, structural complexity and internal states terms) and grammaticality; that is, the extent to which utterances follow the grammatical rules of a language. The participants in the study were 40 Russian-Cypriot Greek (CG) simultaneous bilingual children; their ages ranged from 4;0 to 6;0 (mean 5;2 [years;months]), and they attended kindergartens and primary CG schools where the language of instruction was Greek. The Multilingual Assessment Instrument for Narratives (LITMUS-MAIN; Gagarina et al., 2012; 2015) was used for the data collection. The participants’ language proficiency in Russian was measured using the Russian Proficiency Test for Multilingual Children (RPTMC), while background information was obtained via parental questionnaires and interviews. The narratives were recorded, transcribed and analysed in terms of macro-structure and grammaticality. The analysis of the data showed that heritage children had errors in aspect, case, gender, morphological agreement, subject and object pronoun non-target production, as well as in innovative forms of words (nouns and verbs). There was non-standard production in terms of words order, prepositions and conjunctions. Overall, it was found that grammaticality was affected by proficiency in the heritage language, but there was no correlation with macro-structure measures. Narrative production and comprehension, macro-structure, were affected by the mode of narration.